The Influence of Illustrated Story Media and Learning Activities on The Paragraphs Writing Ability on The Sidewa Class V SDN 2 Kotabumi - Fatmawaty S., Merry; Jaya, Wayan Satria; Supriyono, Supriyono; Herlisya, Destia (IJLHE: International Journal of Language, Humanities, and Education, 2020)
This study aims to describe the effect of using illustrated story media and learning activities on the ability to write paragraphs of fifth grade students at SDN 2 Kotabumi Tengah. The method used in this paper uses the correlational method, meaning that data is collected after all the events in question take place. The techniques used in collecting research data are questionnaires, tests, and observations. Research data analysis techniques include requirements analysis test, statistical analysis, and research hypothesis testing techniques. The results of the study can be concluded that, (1) there is a positive and significant relationship between illustrated story media and the ability to write paragraphs, indicated by a correlation coefficient of 15.88, (2) there is a positive and significant relationship between learning activities and the ability to write paragraphs. indicated by a correlation coefficient of 13.70, (3) there is a positive and significant relationship between the influence of the use of illustrated story media and learning activities on the ability to write paragraphs which is indicated by a correlation coefficient of 16.74, (4) the interaction of students who have learning activities low grade students and taught using pictures have the highest average paragraph writing ability of 10.13.